Newton's laws and their application in public health - Oyola García, Alfredo Enrique (2016)
Traditionally, we have learned that a disaster occurs when a system does not have sufficient capacity to respond to an adverse event. However, this definition does not consider the time in which this variable should be measured. Some civil defense law tells us that after 72 hours (time) it is feasible to declare the emergency and receive external support, that is, in this period of time the response actions are implemented (interventions), evaluated and, if the In this case, it is accepted that it has exceeded the system's responsiveness.